2017
DOI: 10.1016/j.eucr.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Screw as a Bladder Foreign Body

Abstract: Foreign bodies in the bladder are among the strangest differential diagnoses in the lower urinary tract symptoms (LUTS) and may be missed in initial medical evaluations. We present a 63-year-old man who was visited in the emergency department because of obstructive and irritative lower urinary tract symptoms. Two months earlier, he had a pelvic fracture due to motor vehicle accident and underwent an open reduction and internal fixation of the pubic rami and right acetabulum by an anterior ilioinguinal approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…In the case of Peled et al [4], there was a bladder injury at the time of injury; therefore, the possibility that the screw entered the injured area could not be excluded. Hosseini et al [3] also reported a case of delayed bladder perforation due to screw loosening 7 weeks after pelvic surgery, which was treated with cystoscopic screw removal. Unlike the above cases, our case was accompanied by breakage of the symphyseal plate and loosening of the screw, and the presence of a screw in the bladder was confirmed by a cystoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Peled et al [4], there was a bladder injury at the time of injury; therefore, the possibility that the screw entered the injured area could not be excluded. Hosseini et al [3] also reported a case of delayed bladder perforation due to screw loosening 7 weeks after pelvic surgery, which was treated with cystoscopic screw removal. Unlike the above cases, our case was accompanied by breakage of the symphyseal plate and loosening of the screw, and the presence of a screw in the bladder was confirmed by a cystoscope.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only three cases of bladder perforation due to screw loosening have been reported world-Journal of Trauma and Injury 2021 Dec 22. [Epub ahead of print] wide [2][3][4]. Moreover, delayed bladder perforation due to screw loosening after fixation of the symphyseal plate has not been reported in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…In instances of self-insertion for sexual gratification or other related patient reasons, psychiatric disorders like dementia, drug intoxication, or associated conditions, a high index of suspicion is often required, as seen in our case scenario. Several retrospective studies have documented that lower urinary tract foreign bodies can be caused by self-infliction, migratory, iatrogenic causes, sexual abuse, psychiatric illnesses, or other rare causes [6,[8][9][10][11][12][13][14]. Some authors report varying percentages in the incidence of the entry route [6][7][8][9][10][11][12][13][14].…”
Section: Case Presentationmentioning
confidence: 99%
“…Several retrospective studies have documented that lower urinary tract foreign bodies can be caused by self-infliction, migratory, iatrogenic causes, sexual abuse, psychiatric illnesses, or other rare causes [6,[8][9][10][11][12][13][14]. Some authors report varying percentages in the incidence of the entry route [6][7][8][9][10][11][12][13][14]. The true incidence of FBs may vary.…”
Section: Case Presentationmentioning
confidence: 99%
“…These include needles, pins, pen tip, plastic cup, olive seeds and so on. These are usually associated with old age, poor mental condition, intoxication or for sexual stimulation 2. A proper history is vital in these cases as the history of FB insertion is often not revealed by the patient.…”
Section: Introductionmentioning
confidence: 99%